Composite copper foil and preparation method and application thereof
By modifying the self-assembled molecular transition layer on the surface of the magnetron sputtering metal layer of the composite copper foil and optimizing the water plating treatment process, the problem of the poor bonding force between the water plating layer and the magnetron sputtering substrate in the composite copper foil is solved, and its mechanical and electrical properties are improved.
Patent Information
- Application Number
- CN202510046741.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The adhesion between the existing composite copper foil in the water-electroplating layer and the magnetron sputtering substrate is poor, resulting in the plating layer being easily shed and lithium dendrites forming, affecting battery performance.
The molecular self-assembly strategy is used to modify the self-assembly molecular transition layer on the surface of the magnetron sputtering metal layer, enhance the adhesion between the water plating layer and the magnetron sputtering layer, and optimize the water plating treatment process and formula to form a micro-nano array structure with adjustable surface morphology.
The mechanical and electrical properties of composite copper foil are significantly improved, the coating is removed, and the uniformity of lithium deposition and battery circulation performance are improved.
Smart Images

Figure CN119824415A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy materials, and in particular to a composite copper foil and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of electric vehicles and portable rechargeable devices, the demand and performance requirements for lithium-ion batteries have gradually increased. Anode-free lithium metal batteries have attracted widespread attention due to their high energy density, low cost, and easy production, and are currently an ideal substitute for lithium-ion batteries. However, the copper current collector accounts for more than 25% of the total weight of the anode-free battery, which seriously reduces the energy and power density. Composite copper foil, as a new type of negative electrode current collector for lithium-ion batteries, has the significant advantages of low cost, high safety, and light weight, which has significant advantages in reducing production costs and increasing battery energy density.
[0003] Usually, the composite copper foil has a sandwich structure, with a polymer as the substrate, such as polypropylene, polyethylene terephthalate or polyimide, and a copper layer as the conductive layer prepared on both sides by magnetron sputtering, vacuum evaporation, chemical plating or water electroplating. However, the interaction between the polymer substrate and the copper layer, and the copper layer and the electroplating layer is weak, resulting in a large square resistance of the composite current collector and poor structural stability, which seriously restricts the performance improvement of the negative electrode-free battery. Therefore, how to enhance the bonding force of each interface layer and obtain a composite copper foil with stable performance and high efficiency is an urgent problem to be solved.
[0004] Sun Hao's team (Adv. Mater. 2024, 36, 2407648) regulated the molecular structure of the base polyamide urea and used the strong coordination between NH, C=O groups and the copper layer to give the composite current collector excellent interfacial stability. In addition, Pan Junan's team (Adv. Funct. Mater. 2024, 2310925) enhanced the metal / polymer interface strength by introducing a chromium layer into polyethylene terephthalate. The above strategies are all aimed at improving the bonding force between the polymer and the metal layer in the one-step preparation process. However, the one-step method for preparing composite copper foil has high production costs and low efficiency.
[0005] The "two-step method" combining magnetron sputtering and water electroplating has the advantages of high production efficiency and low cost, but its main problem is that the water electroplating layer has poor adhesion to the magnetron sputtering or chemical plating substrate. The plating layer is easy to break or fall off as a whole after being thickened by water electroplating. Even if it can be combined with subsequent processing and battery circulation, the water electroplating layer is extremely easy to fall off; in addition, the surface of the water electroplating layer in the traditional process is too smooth and flat, which is extremely uneven during the lithium deposition process, which easily leads to the formation of lithium dendrites, low coulomb efficiency and possible puncture of the diaphragm, resulting in a shortened battery life. CN115700295A discloses a continuous preparation process for a PET composite copper foil roll. After magnetron sputtering on the PET surface, a pulse electroplating strategy is used to prepare a composite copper foil with a thickness of 6.5-7.5 microns. Fang Huiming et al. (Electroplating & Finishing, 2024, 43, 25-31) changed the electroplating solution formula by screening the accelerator, inhibitor and leveler of copper electroplating in the sulfate system, and plated copper with a thickness of 1-2 microns on both sides of the ultra-thin organic polymer film. However, the above research only changed the electroplating process and formula, and did not fundamentally enhance the bonding force between the magnetron sputtering layer and the water electroplating layer. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a composite copper foil and a preparation method and application thereof, which can enhance the bonding performance between water electroplating and magnetron sputtering substrates and improve the mechanical and electrical properties of the composite copper foil.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a composite copper foil, the preparation method comprising the following steps:
[0009] (1) depositing a copper layer on a polymer substrate by magnetron sputtering, and then coating the polymer substrate on which the copper layer is deposited with a self-assembled molecular transition layer by liquid immersion treatment or vapor deposition treatment to obtain a composite structure layer;
[0010] (2) The composite structure layer obtained in step (1) is subjected to water electroplating treatment and post-treatment in sequence to obtain the composite copper foil.
[0011] The preparation method of the composite copper foil provided by the present invention adopts a molecular self-assembly strategy to modify a chemical molecule with strong binding force with metal copper on the surface of the magnetron sputtering metal layer as a transition layer, thereby enhancing the bonding force with the water electroplating layer. The self-assembled molecular transition layer is coated by liquid phase immersion treatment or vapor phase deposition treatment, which has the advantages of low cost and suitability for large-scale production; the constructed nanoscale molecular transition layer does not increase the weight and thickness, and can significantly improve the bonding force between the magnetron sputtering layer and the water electroplating layer by chemical bond force, thereby avoiding the shedding of the coating.
[0012] Preferably, the polymer substrate in step (1) comprises PET.
[0013] Preferably, the thickness of the polymer substrate in step (1) is 3-5 μm, for example, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0014] Preferably, the deposition thickness of the copper layer in step (1) is 0.5-1.2 μm, for example, 0.5, 0.6, 0.7, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0015] The depositing of the copper layer on the polymer substrate of the present invention refers to depositing the copper layer on both sides of the polymer substrate by magnetron sputtering.
[0016] Preferably, before coating the self-assembled molecular transition layer in step (1), the step also includes cleaning and drying the polymer substrate on which the copper layer is deposited.
[0017] Preferably, the cleaning comprises cleaning with dilute hydrochloric acid and cleaning with acetone performed sequentially.
[0018] Preferably, the drying is carried out by using high-purity nitrogen.
[0019] The “high purity nitrogen” refers to nitrogen with a purity of ≥ 99.99%.
[0020] Preferably, the reagents used in the liquid phase immersion treatment and the vapor phase deposition treatment in step (1) are both organic solutions of copper-philic self-assembling molecules.
[0021] Preferably, the concentration of the chrophilic self-assembling molecules in the organic solution of the chrophilic self-assembling molecules is 2.5-15 mmol / L, for example, 2.5 mmol / L, 4 mmol / L, 5 mmol / L, 8 mmol / L, 10 mmol / L, 12 mmol / L or 15 mmol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] Preferably, the copper-philic self-assembling molecules in the organic solution of copper-philic self-assembling molecules include any one of thiocyanuric acid, melamine, cyanuric acid, benzotriazole or 2-mercaptobenzothiazole, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of thiocyanuric acid and melamine, a combination of cyanuric acid, benzotriazole and 2-mercaptobenzothiazole, a combination of thiocyanuric acid, melamine, cyanuric acid and benzotriazole, or a combination of thiocyanuric acid, melamine, cyanuric acid, benzotriazole and 2-mercaptobenzothiazole.
[0023] The copper-philic self-assembly molecules of the present invention are conductive molecules with binding force to copper metal, which can enhance the bonding performance of water electroplating and magnetron sputtering substrates. The formed self-assembly molecular transition layer has multiple copper-philic molecular groups, such as S, N, O and other anchoring groups, and the transition layer is thin and light, uniform and dense, with a size of 5-10nm, good conductivity and light weight.
[0024] Preferably, the solvent in the organic solution of the cuprophilic self-assembling molecules includes any one of N-methylpyrrolidone, ethanol, N,N-dimethylformamide, tetrahydrofuran, dimethyl sulfoxide or acetone, or a combination of at least two of them. Typical but non-limiting combinations include a combination of N-methylpyrrolidone and ethanol, a combination of N,N-dimethylformamide, tetrahydrofuran, dimethyl sulfoxide and acetone, or a combination of N-methylpyrrolidone, ethanol, N,N-dimethylformamide, tetrahydrofuran, dimethyl sulfoxide and acetone.
[0025] The solvent in the organic solution of the chalcophilic self-assembly molecules may also be other liquids capable of dissolving the chalcophilic self-assembly molecules.
[0026] Preferably, the specific steps of the liquid phase immersion treatment in step (1) include: immersing the polymer substrate on which the copper layer is deposited in an organic solution of copper-philic self-assembly molecules, and then washing with ethanol and drying with high-purity nitrogen gas after taking it out.
[0027] Preferably, the temperature of the organic solution of the cuprophilic self-assembling molecules is 45-65°C, for example, 45°C, 50°C, 55°C, 60°C or 65°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] Preferably, the soaking time is 3-60 min, for example, 3 min, 5 min, 10 min, 20 min, 30 min, 40 min, 50 min or 60 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the specific steps of the vapor deposition treatment in step (1) include: placing a container containing the organic solution of the copper-philic self-assembly molecules in an oven, and suspending the polymer substrate with the deposited copper layer on the top of the container for vapor deposition.
[0030] Preferably, the vapor deposition temperature is 45-120° C. and the time is 55-65 min.
[0031] The temperature of the vapor deposition is 45-120° C., for example, 45° C., 50° C., 80° C., 100° C. or 120° C., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0032] The vapor deposition time is 55-65 min, for example, 55 min, 58 min, 60 min, 62 min or 65 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, the composition of the electrolyte used for the water electroplating treatment in step (2) includes: 0.02-0.04 mol / L copper sulfate, 0.1-0.4 mol / L sodium hypophosphite, 0.0015-0.005 mol / L nickel sulfate, 0.03-0.07 mol / L trisodium citrate, 0.3-1 mol / L boric acid and 1-15 g / L polyethylene glycol, and the pH value of the electrolyte is adjusted to 7-9 using 4 mol / L sodium hydroxide solution.
[0034] The concentration of copper sulfate in the electrolyte is 0.02-0.04 mol / L, for example, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.035 mol / L or 0.04 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] The concentration of sodium hypophosphite in the electrolyte is 0.1-0.4 mol / L, for example, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.3 mol / L or 0.4 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] The concentration of nickel sulfate in the electrolyte is 0.0015-0.005 mol / L, for example, it can be 0.0015 mol / L, 0.002 mol / L, 0.003 mol / L, 0.004 mol / L or 0.005 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] The concentration of trisodium citrate in the electrolyte is 0.03-0.07 mol / L, for example, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L or 0.07 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] The concentration of boric acid in the electrolyte is 0.3-1 mol / L, for example, 0.3 mol / L, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L or 1 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] The concentration of polyethylene glycol in the electrolyte is 1-15 g / L, for example, 1 g / L, 3 g / L, 5 g / L, 8 g / L, 10 g / L, 12 g / L or 15 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] The pH value of the electrolyte is 7-9, for example, 7, 7.5, 8, 8.5 or 9, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0041] The electrolyte used in the water electroplating treatment may also be a copper pyrophosphate system.
[0042] Preferably, the temperature of the electrolyte used for the water electroplating treatment in step (2) is 60-80°C, for example, it can be 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] Preferably, in the water electroplating treatment in step (2), the composite structure layer is used as a working electrode, and a copper sheet of the same area is polished and used as a counter electrode, and the electrode spacing is 2-5 cm.
[0044] The electrode spacing is 2-5 cm, for example, 2 cm, 2.5 cm, 3 cm, 4 cm or 5 cm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0045] The water electroplating process may also be a three-electrode system.
[0046] Preferably, a magnet is added for stirring during the water electroplating treatment in step (2).
[0047] Preferably, the current density of the water electroplating treatment in step (2) is 1-4 mA / cm 2 , the deposition time is 5-30min.
[0048] The current density of the water electroplating treatment is 1-4 mA / cm 2 , for example, it can be 1mA / cm 2 , 2.3mA / cm 2 , 3mA / cm 2 , 3.5mA / cm 2 or 4mA / cm 2 , but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0049] The deposition time of the water electroplating treatment is 5-30 minutes, for example, it can be 5 minutes, 10 minutes, 15 minutes, 20 minutes or 30 minutes, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0050] The present invention develops a micro-nano array structure with adjustable surface morphology by optimizing the water electroplating treatment process and formula, thereby improving the mechanical and electrical properties of the composite copper foil. The prepared water electroplating layer is divided into a flat base layer and a copper-nickel alloy micro-nano array layer, wherein the base layer can enhance the mechanical properties and provide structural support; the copper-nickel alloy micro-nano array layer can, on the one hand, slow down the formation of lithium dendrites and form a flat and uniform lithium plating layer during the cycle process, and on the other hand, can enhance the affinity of lithium deposition by mechanical interlocking of the micro-nano cavity and the initial nucleated lithium, and the micro-nano structure cavity can effectively reduce the stress effect caused by the volume expansion during the lithium cycle.
[0051] Preferably, the post-treatment in step (2) includes sequentially washing with deionized water, drying with high-purity nitrogen, stamping and vacuum drying.
[0052] In a second aspect, the present invention provides a composite copper foil, which is prepared by the method for preparing the composite copper foil according to the first aspect.
[0053] The composite copper foil provided by the present invention can enhance the bonding force between the magnetron sputtering metal layer and the water electroplating layer by modifying the self-assembled molecular transition layer on the surface of the magnetron sputtering metal layer, thereby avoiding the shedding of the plating layer; at the same time, the self-assembled molecular transition layer is a nanoscale transition layer, which will not cause changes in weight and volume, and the surface density of the composite copper foil is low.
[0054] In a third aspect, the present invention provides an application of the composite copper foil as described in the second aspect, wherein the composite copper foil is used as a lithium-ion battery electrode material and an electronic component material.
[0055] The composite copper foil provided by the present invention is used as a current collector to assemble a half-cell, and the interface transmission impedance is smaller; in addition, it has a micro-nano array structure with adjustable surface morphology, which is conducive to the uniform deposition of lithium metal, reduces the formation of lithium dendrites, and helps to improve the battery cycle performance.
[0056] Preferably, when the composite copper foil is used as a lithium-ion battery electrode material, the steps of preparing a button-type full battery include:
[0057] The composite copper foil is used as the positive electrode and the lithium metal sheet is used as the negative electrode. An ether electrolyte is used to assemble a button battery, and then the shell is encapsulated to obtain a half-cell; lithium metal is electrodeposited on the surface of the composite copper foil in the half-cell, and the obtained lithium-plated composite copper foil is used as the negative electrode. The ternary nickel-cobalt-manganese electrode or the lithium iron phosphate electrode is used as the positive electrode. A lipid or ether electrolyte is used to assemble a button full battery.
[0058] Preferably, during the assembly of the button cell, a polypropylene separator with a thickness of 25 μm is used to separate the positive and negative electrodes.
[0059] Preferably, the composition of the ether electrolyte includes: 1M LiTFSI, DOL and DME in a volume ratio of 1:1, and 2wt% LiNO3.
[0060] Preferably, the specific steps of electrodepositing lithium metal include: placing the half-cell in an electrical test cabinet and conducting the test at 0.5-1.5 mA / cm 2 The current density is discharged, and 0.5-5mAh / cm is deposited on the surface of the composite copper foil. 2 Lithium metal.
[0061] The current density is 0.5-1.5 mA / cm 2 , for example, it can be 0.5 mA / cm 2 , 0.8mA / cm 2 , 1mA / cm 2 , 1.2mA / cm 2 or 1.5mA / cm 2 , but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0062] The energy density of the electrodeposited lithium metal is 0.5-5 mAh / cm 2 , for example, it can be 0.5 mAh / cm 2 、1mAh / cm 2 , 2mAh / cm 2 、3mAh / cm 2 or 5mAh / cm 2 , but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0063] The lithium-plated composite copper foil obtained after the electrodeposition of lithium metal is used as a negative electrode after being rinsed and dried by DME.
[0064] Preferably, during the assembly process of the button-type full battery, a polypropylene separator with a thickness of 25 μm is used to separate the positive and negative electrodes.
[0065] Preferably, when the composite copper foil is used as an electrode material for a lithium-ion battery, in the step of preparing a soft-pack full battery, copper sheets are used to weld and connect the two sides of the composite copper foil, and the composite copper foil is used as a negative electrode after stamping.
[0066] Since the polymer substrate in the middle of the composite copper foil has poor conductivity, copper sheets are usually used to weld and connect the two sides of the composite copper foil. After preparation, it is stamped and used as the negative electrode. The ternary nickel-cobalt-manganese electrode or lithium iron phosphate electrode is used as the positive electrode, and an appropriate basic electrolyte is added to assemble a full battery for testing.
[0067] Compared with the prior art, the present invention has the following beneficial effects:
[0068] (1) The preparation method of the composite copper foil provided by the present invention adopts a molecular self-assembly strategy to modify a chemical molecule with strong binding force with metal copper on the surface of the magnetron sputtering metal layer as a transition layer, thereby enhancing the bonding force with the water electroplating layer. The self-assembled molecular transition layer is coated by liquid immersion treatment or vapor deposition treatment, which has the advantages of low cost and suitability for large-scale production; the constructed nanoscale molecular transition layer does not increase the weight and thickness, and can significantly improve the bonding force between the magnetron sputtering layer and the water electroplating layer by chemical bond force, thereby avoiding the shedding of the coating.
[0069] (2) The present invention develops a micro-nano array structure with adjustable surface morphology by optimizing the water electroplating process and formula, thereby improving the mechanical and electrical properties of the composite copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 This is an optical image of a copper layer deposited on the surface of a polymer substrate provided in Example 1 of the present invention by magnetron sputtering;
[0071] Figure 2 This is an optical image of the surface of the magnetron sputtering layer provided in Example 1 of the present invention after being coated with thiocyanuric acid;
[0072] Figure 3 is an optical image of the surface of the composite copper foil provided in Example 1 of the present invention;
[0073] Figure 4 is a Fourier transform infrared spectrum of the surface of the magnetron sputtering layer provided in Example 1 of the present invention after being coated with thiocyanuric acid;
[0074] Figure 5 is a graph showing the change in interface transmission impedance of a half-cell provided in Example 1 of the present invention;
[0075] Figure 6 is a scanning electron microscope cross-sectional view of the composite copper foil after lithium plating provided in Example 1 of the present invention;
[0076] Figure 7 is a SEM image of a copper layer deposited on the surface of a polymer substrate provided in Example 4 of the present invention by magnetron sputtering;
[0077] Figure 8 is a SEM image of the composite copper foil provided in Example 4 of the present invention;
[0078] Fig. 9 is a SEM image of the composite copper foil provided in Example 5 of the present invention;
[0079] Fig.10 is an optical image of the composite copper foil provided in Comparative Example 1 of the present invention;
[0080] Fig.11 This is a scanning electron microscope cross-sectional view of the composite copper foil after lithium plating provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0081] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0082] Example 1
[0083] This embodiment provides a composite copper foil, and the preparation method of the composite copper foil comprises the following steps:
[0084] (1) A 1 μm copper layer is deposited on both sides of a 4 μm thick PET substrate by magnetron sputtering, and then washed with dilute hydrochloric acid, washed with acetone, and dried with high-purity nitrogen in sequence; then, the polymer substrate on which the copper layer is deposited is immersed in an ethanol solution of thiocyanate at a temperature of 50° C. and a concentration of 5 mmol / L for 5 min, and a self-assembled molecular transition layer is coated on the polymer substrate on which the copper layer is deposited, and then, after being taken out, washed with ethanol and dried with high-purity nitrogen to obtain a composite structure layer;
[0085] (2) The composite structure layer obtained in step (1) is used as a working electrode, and a copper sheet of the same area is polished as a counter electrode, and the electrode spacing is 3 cm; the temperature of the electrolyte used is 75°C, and the composition of the electrolyte includes: 0.03 mol / L copper sulfate, 0.24 mol / L sodium hypophosphite, 0.0024 mol / L nickel sulfate, 0.05 mol / L trisodium citrate, 0.5 mol / L boric acid and 6 g / L polyethylene glycol, and the pH value of the electrolyte is adjusted to 8 using 4 mol / L sodium hydroxide solution; a magnetic bar is added for stirring, and the current density is 2.3 mA / cm 2 The composite copper foil is subjected to water electroplating for 20 minutes; then, it is washed with deionized water, dried with high-purity nitrogen, stamped and vacuum dried to obtain the composite copper foil.
[0086] The optical image of the polymer substrate surface after the copper layer is deposited by magnetron sputtering in this embodiment is as follows: Figure 1 As shown, the optical image of the magnetron sputtering layer after coating with polythiocyanate is as follows Figure 2 As shown, the optical image of the composite copper foil surface is as follows Figure 3 As shown, it can be seen that the surface of the polymer substrate on which the copper layer was deposited turned yellow after being modified with thiocyanate. After further electroplating treatment, the electroplated layer on the surface did not fall off and the color was relatively uniform.
[0087] The Fourier transform infrared spectrum of the magnetron sputtering layer after coating with thiocyanate is shown in the figure below. Figure 4 As shown, at 1440cm -2 The characteristic of tridentate thio compounds appeared at 1238 cm -2 The characteristic peaks of thiol and covalent metal-sulfur bond formation are confirmed. These characteristic peaks of thiocyanate binding to copper further illustrate that the self-assembled molecules achieve uniform coating on the magnetron sputtered metal layer.
[0088] After testing, the surface density of the composite copper foil is 4.63mg / cm 2 , indicating that the self-assembled molecular transition layer is a nanoscale transition layer and does not bring about changes in weight and volume. The surface density of the composite copper foil prepared is lower than that of 8.55 mg / cm 2 The commercially available composite copper foil has a surface density reduced by about 45.8%.
[0089] The composite copper foil is used as the positive electrode, the lithium metal sheet is used as the negative electrode, and the ether electrolyte of 1M LiTFSI, 1:1 volume ratio of DOL and DME, and 2wt% LiNO3 is used. The positive and negative electrodes are separated by a 25μm thick polypropylene separator to assemble a sandwich structure 2032 button battery, and then a hydraulic press is used to encapsulate the shell to obtain a half-cell. The interface transmission impedance change diagram is shown in FIG. Figure 5 As shown in the figure, it can be seen that the interface transmission impedance of the half-cell assembled by using the composite copper foil provided in this embodiment as the current collector is smaller than that of the half-cell assembled by using the commercially available composite copper foil.
[0090] The half-cell was placed in an electrical test cabinet and tested at 1.5 mA / cm 2 Lithium was deposited at a current density of 2.5 mAh / cm 2 After disassembling, DME was used for cleaning and drying, and a scanning electron microscope was used for observation. The scanning electron microscope cross-sectional view of the composite copper foil after lithium plating prepared in this embodiment is as follows: Figure 6 As shown, it can be seen that the magnetron sputtering layer is tightly bonded to the electroplating layer, and because the micro-nano cavities of the electroplating layer can be mechanically interlocked with the initially deposited lithium, the bonding force between the electroplating layer and the lithium deposition layer is strong, and the high specific surface area also inhibits dendrite growth, and the deposited lithium is dense and uniform.
[0091] The tensile mechanical properties were tested by a tensile testing machine. The results showed that the tensile strength of the composite copper foil prepared in this embodiment was enhanced by about 45% compared with the untreated commercial composite copper foil. This was mainly due to the π-π force and hydrogen bond between thiocyanate molecules, as well as the coordination bond force between the self-assembled molecules and copper. The half-cell performance of the lithium sheet assembly was further tested. The composite copper foil prepared in this embodiment can run stably for more than 300 cycles without attenuation. The obtained lithium-plated composite copper foil was used as the negative electrode, and the lithium iron phosphate electrode was used as the positive electrode. The assembled button-type full battery can run stably for 500 cycles without capacity attenuation, which is better than the untreated composite copper foil.
[0092] Example 2
[0093] This embodiment provides a composite copper foil, and the preparation method of the composite copper foil comprises the following steps:
[0094] (1) A 0.5 μm copper layer is deposited on both sides of a 3 μm thick PET substrate by magnetron sputtering, and then washed with dilute hydrochloric acid, washed with acetone, and dried with high-purity nitrogen in sequence; then, the polymer substrate on which the copper layer is deposited is immersed in an acetone solution of melamine at a temperature of 45° C. and a concentration of 2.5 mmol / L for 60 min, and a self-assembled molecular transition layer is coated on the polymer substrate on which the copper layer is deposited, and then, after being taken out, washed with ethanol and dried with high-purity nitrogen to obtain a composite structure layer;
[0095] (2) The composite structure layer obtained in step (1) is used as a working electrode, and a copper sheet of the same area is polished as a counter electrode, and the electrode spacing is 2 cm; the temperature of the electrolyte used is 60°C, and the composition of the electrolyte includes: 0.02 mol / L copper sulfate, 0.1 mol / L sodium hypophosphite, 0.0015 mol / L nickel sulfate, 0.03 mol / L trisodium citrate, 0.3 mol / L boric acid and 1 g / L polyethylene glycol, and the pH value of the electrolyte is adjusted to 7 using 4 mol / L sodium hydroxide solution; a magnetic bar is added for stirring, and the current density is 1 mA / cm 2 The composite copper foil is subjected to water electroplating for 30 minutes; then, it is washed with deionized water, dried with high-purity nitrogen, stamped and vacuum dried to obtain the composite copper foil.
[0096] In this embodiment, the polymer substrate on which the copper layer is deposited is coated with a self-assembled molecular transition layer and then further treated with water electroplating. Tests have shown that the surface water electroplating layer does not fall off and the color is relatively uniform. Copper sheets are used to weld the two sides of the composite copper foil, and a soft-pack full battery is prepared as the negative electrode after stamping. After testing, a soft-pack battery using lithium iron phosphate as the positive electrode and an ether-based electrolyte, the electrolyte composition is: 1M LiTFSI, DOL / DME=1:1v / v%, 2wt% LiNO3, 10wt% FEC, 0.05% PPS, and the capacity retention rate is 85% after running 50 cycles.
[0097] Example 3
[0098] This embodiment provides a composite copper foil, and the preparation method of the composite copper foil comprises the following steps:
[0099] (1) A 1.2 μm copper layer is deposited on both sides of a 5 μm thick PET substrate by magnetron sputtering, and then washed with dilute hydrochloric acid, washed with acetone, and dried with high-purity nitrogen in sequence; then, the polymer substrate on which the copper layer is deposited is immersed in a tetrahydrofuran solution of benzotriazole at a temperature of 65° C. and a concentration of 15 mmol / L for 3 min, and a self-assembled molecular transition layer is coated on the polymer substrate on which the copper layer is deposited, and then, after being taken out, washed with ethanol and dried with high-purity nitrogen to obtain a composite structure layer;
[0100] (2) The composite structure layer obtained in step (1) is used as a working electrode, and a copper sheet of the same area is polished as a counter electrode, and the electrode spacing is 5 cm; the temperature of the electrolyte used is 80°C, and the composition of the electrolyte includes: 0.04 mol / L copper sulfate, 0.4 mol / L sodium hypophosphite, 0.005 mol / L nickel sulfate, 0.07 mol / L trisodium citrate, 1 mol / L boric acid and 15 g / L polyethylene glycol, and the pH value of the electrolyte is adjusted to 9 using 4 mol / L sodium hydroxide solution; a magnetic bar is added for stirring, and the current density is 4 mA / cm 2 The composite copper foil is subjected to water electroplating for 5 minutes; then, it is washed with deionized water, dried with high-purity nitrogen, stamped and vacuum dried to obtain the composite copper foil.
[0101] In this embodiment, the polymer substrate on which the copper layer is deposited is coated with a self-assembled molecular transition layer and then subjected to further water electroplating treatment. Tests have shown that the surface water electroplating layer does not fall off and the color is relatively uniform. Tests have shown that the lithium sheet assembled half-cell can stably operate for 250 cycles, which is better than the commercial composite copper foil that has not undergone any treatment.
[0102] Example 4
[0103] The present embodiment provides a composite copper foil. The difference between the preparation method of the composite copper foil and that of Example 1 is that in step (1), a container containing an ethanol solution of thiocyanate with a concentration of 5 mmol / L is placed in an oven, and the polymer substrate of the deposited copper layer is suspended on the top of the container for vapor deposition at a temperature of 50°C and a time of 60 min. The rest is the same as that of Example 1.
[0104] The SEM image of the copper layer deposited on the polymer substrate surface by magnetron sputtering in this embodiment is as follows: Figure 7 As shown in the figure, it can be seen that the surface is too flat, which can easily cause dendrite growth during lithium deposition. Figure 8As shown in the figure, it can be seen that the surface of the composite copper foil is a copper-nickel alloy micro-nano array structure, which can reduce the lithium nucleation overpotential and local current density in lithium battery applications, and has a significant effect on improving the reversibility and kinetics of the lithium metal deposition-stripping process.
[0105] In this embodiment, the polymer substrate on which the copper layer is deposited is coated with a self-assembled molecular transition layer and then subjected to further water electroplating treatment. Tests have shown that the surface water electroplating layer does not fall off and the color is relatively uniform. Tests have shown that its electrochemical properties are almost consistent with those prepared by the liquid phase method of coating thiocyanate, and both can operate stably for more than 300 cycles, and its impedance is much lower than that of untreated commercial copper foil.
[0106] Example 5
[0107] This embodiment provides a composite copper foil. The difference between the preparation method of the composite copper foil and that of Embodiment 1 is that the electrolyte in step (2) does not contain nickel sulfate, and the rest is the same as that of Embodiment 1.
[0108] The SEM image of the composite copper foil obtained in this embodiment is as follows: Fig. 9 As shown in the figure, it can be seen that the surface of the composite copper foil is a micro-nano protrusion structure, which is greatly improved compared to the smoothness of the polymer substrate surface on which the copper layer is deposited after magnetron sputtering.
[0109] In this embodiment, the polymer substrate on which the copper layer is deposited is coated with a self-assembled molecular transition layer and then subjected to further water electroplating treatment. Tests have shown that the surface water electroplating layer does not fall off and the color is relatively uniform. Tests have shown that it can stably operate for 220 cycles during a half-battery cycle, indicating that compared with water electroplating treatment using an electrolyte with added nickel sulfate, the surface morphology of the water electroplating layer does not form an array structure, and the performance of the resulting battery is slightly reduced.
[0110] Example 6
[0111] This embodiment provides a composite copper foil. The difference between the preparation method of the composite copper foil and that of embodiment 1 is that the current density of the water electroplating treatment in step (2) is adjusted to 0.5 mA / cm 2 Except for this, the rest are the same as in Example 1.
[0112] In this embodiment, the polymer substrate on which the copper layer is deposited is coated with the self-assembled molecular transition layer and then further treated with water electroplating. Tests have shown that the surface water electroplating layer cannot grow into a rough array structure, but rather a layer of particle film. Tests have shown that the lithium assembled half-cell can run stably for 200 cycles, indicating that the current density of the water electroplating treatment is too small, which is not conducive to the formation of a surface array structure, resulting in reduced performance of the resulting battery.
[0113] Example 7
[0114] This embodiment provides a composite copper foil. The difference between the preparation method of the composite copper foil and that of embodiment 1 is that the current density of the water electroplating treatment in step (2) is adjusted to 4.5 mA / cm 2 Except for this, the rest are the same as in Example 1.
[0115] In this embodiment, the polymer substrate on which the copper layer is deposited is coated with the self-assembled molecular transition layer and then subjected to further water electroplating treatment. Tests have shown that the surface water electroplating layer is relatively coarse and the array structure is extremely sparse, and the array structure does not grow in many areas. Tests have shown that the half-cell of the lithium sheet can run stably for 200 cycles, indicating that the current density of the water electroplating treatment is too large, which is not conducive to the formation of the surface array structure, resulting in reduced performance of the resulting battery.
[0116] Comparative Example 1
[0117] This comparative example provides a composite copper foil. The difference between the preparation method of the composite copper foil and that of Example 1 is that the polymer substrate on which the copper layer is deposited in step (1) is not coated with a self-assembled molecular transition layer, but is directly used as a working electrode for water electroplating. The rest is the same as that of Example 1.
[0118] The optical image of the composite copper foil obtained in this comparative example is as follows Fig.10 As shown in the figure, it can be seen that the adhesion of the water electroplating layer is poor, and there is a phenomenon of overall shedding or partial breakage. 2 The current density of lithium deposition on the polymer substrate with only magnetron sputtered copper layer is 2.5 mAh / cm 2 After disassembling, DME was used for cleaning and drying, and a scanning electron microscope was used for observation. The scanning electron microscope cross-sectional view of the composite copper foil after lithium plating provided in this comparative example is as follows: Fig.11 As shown, the lithium layer and the substrate are easy to fall off. According to the test, the lithium sheet half-cell begins to decay after about 150 cycles.
[0119] In summary, the preparation method of the composite copper foil provided by the present invention adopts a molecular self-assembly strategy to modify a chemical molecule with strong binding force with metal copper on the surface of the magnetron sputtering metal layer as a transition layer, thereby enhancing the bonding force with the water electroplating layer. The self-assembled molecular transition layer is coated by liquid immersion treatment or vapor deposition treatment, which has the advantages of low cost and suitability for large-scale production; the constructed nanoscale molecular transition layer does not increase the weight and thickness, and can use the chemical bond force to significantly improve the bonding force between the magnetron sputtering layer and the water electroplating layer, thereby avoiding the shedding of the coating.
[0120] The present invention develops a micro-nano array structure with adjustable surface morphology by optimizing the water electroplating treatment process and formula, thereby improving the mechanical properties and electrical properties of the composite copper foil.
[0121] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a composite copper foil, characterized in that: The preparation method comprises the following steps: (1) depositing a copper layer on a polymer substrate by magnetron sputtering, and then coating the polymer substrate on which the copper layer is deposited with a self-assembled molecular transition layer by liquid immersion treatment or vapor deposition treatment to obtain a composite structure layer; (2) The composite structure layer obtained in step (1) is subjected to water electroplating treatment and post-treatment in sequence to obtain the composite copper foil.
2. The preparation method according to claim 1, characterized in that: The polymer substrate in step (1) comprises PET; Preferably, the thickness of the polymer substrate in step (1) is 3-5 μm; Preferably, the deposition thickness of the copper layer in step (1) is 0.5-1.2 μm.
3. The preparation method according to claim 1 or 2, characterized in that: Before the step (1) of coating the self-assembled molecular transition layer, the step also includes the steps of cleaning and drying the polymer substrate on which the copper layer is deposited; Preferably, the cleaning comprises cleaning with dilute hydrochloric acid and cleaning with acetone performed sequentially; Preferably, the drying is carried out by using high-purity nitrogen.
4. The preparation method according to any one of claims 1 to 3, characterized in that The reagents used in the liquid phase immersion treatment and the vapor phase deposition treatment in step (1) are both organic solutions of copper-philic self-assembling molecules; Preferably, the concentration of the copper-philic self-assembly molecules in the organic solution of the copper-philic self-assembly molecules is 2.5-15 mmol / L; Preferably, the copper-philic self-assembling molecules in the organic solution of copper-philic self-assembling molecules include any one of thiocyanuric acid, melamine, cyanuric acid, benzotriazole or 2-mercaptobenzothiazole, or a combination of at least two thereof; Preferably, the solvent in the organic solution of the cuprophilic self-assembly molecules includes any one of N-methylpyrrolidone, ethanol, N,N-dimethylformamide, tetrahydrofuran, dimethyl sulfoxide or acetone, or a combination of at least two thereof.
5. The preparation method according to claim 4, characterized in that: The specific steps of the liquid phase immersion treatment in step (1) include: immersing the polymer substrate deposited with the copper layer in an organic solution of copper-philic self-assembly molecules, and then washing with ethanol and drying with high-purity nitrogen gas after taking it out; Preferably, the temperature of the organic solution of the copper-philic self-assembling molecules is 45-65° C.; Preferably, the soaking time is 3-60 min.
6. The preparation method according to claim 4, characterized in that: The specific steps of the vapor deposition treatment in step (1) include: placing a container containing the organic solution of the copper-philic self-assembly molecules in an oven, and suspending the polymer substrate on which the copper layer is deposited on the top of the container for vapor deposition; Preferably, the vapor deposition temperature is 45-120° C. and the time is 55-65 min.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The electrolyte used in the water electroplating treatment in step (2) comprises: 0.02-0.04 mol / L copper sulfate, 0.1-0.4 mol / L sodium hypophosphite, 0.0015-0.005 mol / L nickel sulfate, 0.03-0.07 mol / L trisodium citrate, 0.3-1 mol / L boric acid and 1-15 g / L polyethylene glycol, and the pH value of the electrolyte is adjusted to 7-9 using 4 mol / L sodium hydroxide solution; Preferably, the temperature of the electrolyte used in the water electroplating treatment in step (2) is 60-80°C; Preferably, in the water electroplating treatment in step (2), the composite structure layer is used as a working electrode, a copper sheet of the same area is used as a counter electrode, and the electrode spacing is 2-5 cm; Preferably, a magnet is added to stir the water during the electroplating process in step (2); Preferably, the current density of the water electroplating treatment in step (2) is 1-4 mA / cm 2 , the deposition time is 5-30min; Preferably, the post-treatment in step (2) includes sequentially washing with deionized water, drying with high-purity nitrogen, stamping and vacuum drying.
8. A composite copper foil, characterized in that: The composite copper foil is prepared by the method for preparing the composite copper foil according to any one of claims 1 to 7.
9. An application of the composite copper foil as claimed in claim 8, characterized in that: The composite copper foil is used as a lithium ion battery electrode material and an electronic component material.
10. The use according to claim 9, characterized in that: When the composite copper foil is used as a lithium-ion battery electrode material, the steps of preparing a button-type full battery include: The composite copper foil is used as the positive electrode, the lithium metal sheet is used as the negative electrode, and an ether electrolyte is used to assemble a button battery, and then the shell is encapsulated to obtain a half-cell; lithium metal is electrodeposited on the surface of the composite copper foil in the half-cell, the obtained lithium-plated composite copper foil is used as the negative electrode, the ternary nickel-cobalt-manganese electrode or the lithium iron phosphate electrode is used as the positive electrode, and a lipid or ether electrolyte is used to assemble a button full battery; Preferably, when the composite copper foil is used as an electrode material for a lithium-ion battery, in the step of preparing a soft-pack full battery, copper sheets are used to weld and connect the two sides of the composite copper foil, and the composite copper foil is used as a negative electrode after stamping.
Citation Information
Patent Citations
Continuous preparation process of PET (polyethylene terephthalate) composite copper foil roll
CN115700295A
Method for preparing self-supporting three-dimensional porous copper film and self-supporting three-dimensional porous copper film
CN107460460A
Flexible copper clad plate
CN108697007A
Metal circuit structure based on FPC and processing method thereof
CN113163588A
Conductive film and pole piece
CN114023972A
Cited By
Production method of copper foil for IC packaging
CN120888920A